2017
DOI: 10.1038/lsa.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the ‘tractor-beam’ pulling force on an optically bound structure

Abstract: Recently, increasing attention has been devoted to mastering a new technique of optical delivery of micro-objects tractor-beam’1, 2, 3, 4, 5, 6, 7, 8, 9. Such beams have uniform intensity profiles along their propagation direction and can exert a negative force that, in contrast to the familiar pushing force associated with radiation pressure, pulls the scatterer toward the light source. It was experimentally observed that under certain circumstances, the pulling force can be significantly enhanced6 if a non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…These results demonstrate that interparticle separation and geometry influence the sign of the optical torque on the arrays. Similarly, it was recently found that the separation and orientation of two optically bound particles could impact the negative forces in a tractor-beam 28 .…”
Section: Resultsmentioning
confidence: 73%
“…These results demonstrate that interparticle separation and geometry influence the sign of the optical torque on the arrays. Similarly, it was recently found that the separation and orientation of two optically bound particles could impact the negative forces in a tractor-beam 28 .…”
Section: Resultsmentioning
confidence: 73%
“…Therefore, this arrangement seems to be well suited for delivering simultaneously multiple particles in the form of optically bound non-spherical structures [13]. Several theoretical studies have also considered the effect of multiple particles on the tractor beam performance [215,216], typically showing an enhancement of the pulling effect. The wavevectors of the two wide Gaussian beams forming the tractor beam shown in Fig.…”
Section: -D Optical Pulling In Tractor Beamsmentioning
confidence: 99%
“…As illustrated by the schematics shown on the right, the direction of particles' motion (pushing or pulling) depends on the vertical inter-particle distance along the y-axis. Adapted under Creative Commons Attribution 4.0 International License from[216].…”
mentioning
confidence: 99%
“…Optical forces on an object due to the exchange of photon momentum with the object [17][18][19][20][21][22][23][24][25][26][27] can move nanoswimmers/ microswimmers along the beam direction. Light propulsion has unique advantages like wireless control, high spatial and temporal precision, and instant response 28 .…”
mentioning
confidence: 99%